Determinants of Academic Achievement Among Islamic Boarding School Students: An Exploration of the Organizational Environment and External Stakeholder Support - Aliyatul Muna; Sisno Riyoko; Anna Widiastuti (Advances in Economics & Financial Studies, 2026)
Purpose: This study aims to examine the effects of the Islamic boarding school environment and parental support on students' academic achievement, as well as the mediating roles of spiritual intelligence and learning motivation. Research Method: This study adopted a quantitative explanatory design. A total of 165 students were selected from a population of 280 using the Slovin formula and purposive sampling. Data were collected through a 10-point Likert-scale questionnaire and academic records, then analyzed using PLS-SEM with SmartPLS 4, including mediation analysis based on the Variance Accounted For (VAF) approach. Results and Discussion: The findings reveal that the Islamic boarding school environment has a positive and significant effect on academic achievement, spiritual intelligence, and learning motivation. Parental support has no significant direct effect on academic achievement but positively influences spiritual intelligence and learning motivation. Both spiritual intelligence and learning motivation significantly enhance academic achievement and mediate the relationship between external factors and academic achievement. Implications: The findings emphasize the need to strengthen the boarding school environment and promote students' spiritual intelligence and learning motivation through collaboration between schools and parents. Originality: This study develops an integrated mediation model combining environmental, family, and psychological factors to explain academic achievement in an Islamic boarding school context.